PEGON ARABIC LETTER STYLING IN CREATION OF BATIK MOTIFS ON CASUAL CLOTHING - Della Putri Mutika Windi; Aan Sudarwanto (Indonesian Institute of the Arts Surakarta, 2025)
Arabic Pegon is an Arabic script used to write regional languages. The Arabic Pegonscript originates from the Javanese Arabic